Quality Improvement Initiatives in Sepsis in an Emerging Country: Does the Institution's Main Source of Income Influence the Results? An Analysis of 21, 103 Patients*. Issue 10 (October 2017) - Machado, Flavia R.; Ferreira, Elaine M.; Sousa, Juliana Lubarino; Silva, Carla; Schippers, Pierre; Pereira, Adriano; Cardoso, Ilusca M.; Salomão, Reinaldo; Japiassu, Andre; Akamine, Nelson; Mazza, Bruno F.; Assunção, Murillo S. C.; et al.
Abstract : Objective: We aimed to assess the results of a quality improvement initiative in sepsis in an emerging setting and to analyze it according to the institutions' main source of income (public or private). Design: Retrospective analysis of the Latin American Sepsis Institute database from 2005 to 2014. Settings: Brazilian public and private institutions. Patients: Patients with sepsis admitted in the participant institutions. Interventions: The quality improvement initiative was based on a multifaceted intervention. The institutions were instructed to collect data on 6-hour bundle compliance and outcomes in patients with sepsis in all hospital settings. Outcomes and compliance was measured for eight periods of 6 months each, starting at the time of the enrollment in the intervention. The primary outcomes were hospital mortality and compliance with 6-hour bundle. Measurements and Main Results: We included 21, 103 patients; 9, 032 from public institutions and 12, 071 from private institutions. Comparing the first period with the eigth period, compliance with the 6-hour bundle increased from 13.5% to 58.2% in the private institutions ( p < 0.0001) and from 7.4% to 15.7% in the public institutions ( p < 0.0001). Mortality rates significantly decreased throughout the program in private institutions, from 47.6% to 27.2% in the eighth period (adjusted odds ratio, 0.45; 95% CI, 0.32–0.64). However, in the public hospitals, mortality diminished significantly only in the first two periods. Conclusion: This quality improvement initiative in sepsis in an emerging country was associated with a reduction in mortality and with improved compliance with quality indicators. However, this reduction was sustained only in private institutions. Abstract : Supplemental Digital Content is available in the text.